Upaya Guru dalam Meningkatkan Kedisiplinan Peserta Didik di C9 School - Putri Maysaroh (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
The purpose of this research is to explain Teacher's Efforts to instill the Value of Discipline and Student Learning Activities in C9 Pekanbaru School. The method used is qualitative, the subjects studied were teachers in C9 Pekanbaru School, amounting to 1 person. The results of the study are based on the results of data analysis obtained after conducting research using observation techniques, interviews and documentation, then there is a relationship of understanding about the efforts of teachers in instilling the value of discipline and student learning activities in Pekanbaru C9 School. Teachers who are in School C9 are expected to continue to accompany students in each learning process and outside the learning process. So that learning objectives can be achieved properly.